Genetic Performance Of Oil Palm (Elaeis Guineensis Jacq.) Progenies From Different Dura Sources In Crosses With Avros Pisifera - Ahmad, Noh (2007)

(untitled)
A total of 40 oil palm (Elaeis guineensis Jacq.) Dura x Pisifera (DxP) progenies derived from the North Carolina Mating Design 1 (NCM1) were evaluated at the MPOB Research Station, Keratong, Pahang in inland soils predominantly of Serdang Series. The Dura sources in this study originated from the Sabah Breeding Programme (SBP) and were crossed with male parents of AVROS Pisifera materials, the descendant of BM119 of Oil Palm Research Station (OPRS) (now Golden Hope), Banting, Selangor. They were laid down in a Randomised Complete Block Design (RCBD) with three replicates, with 16 palms/progeny/replicate in 1994. The materials were evaluated for bunch yield, bunch quality and vegetative traits. The objectives of the study were to evaluate the performance of different Dura sources for bunch yield, bunch quality components and vegetative traits, to estimate genetic variability and heritability, and to assess the phenotypic correlation among the traits. Potential genotypes with high yield were selected for breeding and seed production. Analysis of variance (ANOVA) showed that the Dura sources were not significantly different for bunch yield and yield components, indicating the lack of genetic variability for these characters. However, ANOVA showed greater variability in the bunch quality components of the Dura sources such as mesocarp to fruit ratio (M/F), shell to fruit ratio (S/F), kernel to fruit ratio (K/F) and kernel yield (KY). Significant differences among the Dura sources were also observed in the vegetative traits viz petiole cross-section (PCS), rachis length (RL) and leaflet number (LN). The results indicate that there was still genetic variability among the Dura sources for those traits, even though the materials had undergone many cycles of selection. Three Dura sources DS1 (Banting x Banting), DS2 (Elmina x Elmina) and DS4 (H.Est x H.Est) were identified to be good candidates for further breeding and seed production with FFB yield of more than 130 kg/p/yr and oil yield (OY) of more than 31 kg/p/yr or more than 4.5 tons/ha/yr. ANOVA showed that the Pisifera item in the half-sib families was not significant for most of the traits studied except fruit to bunch ratio (F/B), kernel to bunch ratio (K/B), kernel yield (KY), leaflet length (LL), leaf area (LA) and leaf area index (LAI). This was expected as the AVROS Pisiferas used as males were derived from a small population and they were highly inbred. However, greater variation was observed in the dura within pisifera item. Heritability estimates for bunch yield and its components were generally low, with 2ph of 0-14% and 2dh of 3-32%. Higher estimates were observed in some of the bunch quality components with 2 p h of 0-36% and 2 d h of 0-64%. Generally, vegetative characters had high heritability values, with 2 p h of 0-45% and 2 d h of 9-72%. Phenotypic correlations among the bunch yield components indicate that there exist strong and positive correlation between fresh fruit bunch (FFB) and bunch number (BNO), thus selecting for one character will also improve the other. However, there was also strong negative correlation between BNO and average bunch weight (ABW), indicating that increasing ABW would decrease the BNO and vice versa. This can be an obstacle in the effort to increase bunch yield as the traits cannot be improved simultaneously in the same palm. In this study, it was noted that high FFB yield can be obtained through high BNO and medium ABW. Correlations among bunch quality components and vegetative characters were also observed in this study. Oil yield (OY) correlated positively with bunch yield and its components and also with trunk height (HT). Selecting palms for high OY would also select for vigorous growing palm. Reasonably good general combining ability (GCA) for FFB was observed in three Pisiferas, P1 (0.174/211), P3 (0.174/498) and P11 (0.12/308). For oil to bunch (O/B), the good combiners were P1 (0.174/211), P10 (0.182/305) and P11 (0.12/308). The good combiners for vegetative traits were P6 (0.182/30), P8 (0.182/230) and P9 (0.182/297). For breeding, selection for good combiners can be considered for a single trait or in combination with the others. For instance, P1 (0.174/211) and P11 (0.12/308) were good candidates in selecting for Pisiferas with good GCA for FFB yield and oil to bunch O/B but high GCA values for vegetative characters. Pisiferas P6 (0.182/30), P8 (0.182/230) and P9 (0.182/297) were the right choice to select for less vigorous growing palms since they have good GCA values for lower trunk height (HT), lower trunk diameter (DIA), small petiole cross-section (PCS) and short rachis length (RL). The advantages of having palms with these characters are that they can be planted in higher density and may also increase yield per hectare. The low variability in the materials can be overcome through introgression with other materials. Malaysian Palm Oil Board (MPOB) is actively involved in introgressing newly selected oil palm materials prospected from Africa with the Deli Dura and AVROS Pisiferas to broaden the genetic base. The oil palm germplasm from Nigeria, Cameroon and Zaire after undergoing systematic evaluation and selection were being used to introgress with Deli Dura and AVROS Pisifera as part of the improvement programme. The progenies of the materials were evaluated in a number of field trials in various MPOB Research Stations. It is expected that these materials will be able to contribute to the progress and advancement of the oil palm industry in the future.